2016
DOI: 10.1161/strokeaha.116.013495
|View full text |Cite
|
Sign up to set email alerts
|

Previous Statin Use and High-Resolution Magnetic Resonance Imaging Characteristics of Intracranial Atherosclerotic Plaque

Abstract: Background and Purpose-Although statin use has been linked to the stabilization of systemic atherosclerosis, its effect on symptomatic intracranial atherosclerotic plaques has yet to be explored. We hypothesized that premorbid statin use is associated with plaque instability in intracranial arteries and may lead to differential patterns (size and distribution) of ischemic lesions in patients with acute intracranial atherosclerotic stroke. Methods-One hundred and thirty-six patients with acute infarcts caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…In the present study, there was a trend for the levels of serum ADMA (statin user, 0.68 ± 0.14; statin non-user, 0.72 ± 0.14; p = 0.07) and Lp-PLA 2 (statin user, 133.93 ± 120.29; statin non-user, 153.94 ± 101.99; p = 0.22) to be lower in patients taking statin medication before the onset of the index stroke. Further studies are needed in this context, because a recent high-resolution MRI study showed that the statin dosage prior to stroke was associated with plaque characteristics [29]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was a trend for the levels of serum ADMA (statin user, 0.68 ± 0.14; statin non-user, 0.72 ± 0.14; p = 0.07) and Lp-PLA 2 (statin user, 133.93 ± 120.29; statin non-user, 153.94 ± 101.99; p = 0.22) to be lower in patients taking statin medication before the onset of the index stroke. Further studies are needed in this context, because a recent high-resolution MRI study showed that the statin dosage prior to stroke was associated with plaque characteristics [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, WA lesion /WA reference was used as the plaque burden in our study (Fig. 1), a ratio that has been referred to as the wall area index in previous studies2324. The arterial remodeling ratio was defined as the ratio of the OWA of the selected lesion site (OWA lesion ) to the OWA of the reference site (OWA reference ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the proportion of IS due to plaque rupture was lower among premorbid statin users. Unfortunately, no evaluation was done with regard to the impact of statins on the reduction of the incidence of IS in patients with intracranial atherosclerosis and no clinical improvement was highlighted among premorbid statin-treated patients at 90 days after IS [305]. Many observations demonstrated that pre-treatment with statins improves stroke outcome at 90 days and this benefit is evident across all the stroke subtypes [306,307], as confirmed by the meta-analysis by Biffi et al, especially in patients with small vessel stroke disease, and Ní Chróinín et al [308].…”
Section: Anti-inflammatory Treatments In Is: Evidence From Clinicamentioning
confidence: 99%